Microwave-assisted pyrolysis of crude glycerol - Leong, Swee Kim (2017)
Alternative fuel very important in the renewable energy research. Crude glycerol, an excess by-product of biodiesel production that will led to environment problem was pyrolysed using a microwave heating technique under an oxygen-deficient environment over a bed of coconut shell-based activated carbon catalyst. The batch mode pyrolysis process was carried out at various temperatures and inert carrier gas flow rates to determine the yield of pyrolysis product, i.e solid (bio-char), liquid (bio-oil), and gaseous (bio-gas). The effect of catalyst on product yield was also investigated. Characterization of the pyrolysed products was performed using different instruments. Thermogravimetric analysis (TGA) was performed to determine the thermal characteristic of the bio-char. The morphology of the bio-char produced was characterised by using a field emission scanning electron (FE-SEM) and energy dispersive X-Ray (EDX). The surface area of bio-char was determined via a Brunauer, Emmett and Teller (BET) method. The functional groups of bio-oil were determined by Fourier transform infrared spectroscopy (FT-IR). A gas chromatography- mass spectormetry (GC-MS) was utilised to analyse the liquid products obtained from the experiment. Gas chromatography-thermal conductivity detector (GC-TCD) was used to analysed the bio-gas. Results shows that the increase of pyrolysis temperature led to the increase of bio-gas yield. Highest bio-gas yield was obtained for test case of 100mL/min at 700°C, while the highest bio-liquid yield was obtained for test case of 1000mL/min at 400°C. The experiment results shows that the calorific value for the liquid product was around 14.1MJ/kg and 20.6MJ/kg for gaseous product, this showed that the product that produced from the pyrolysis process had the potential to be an alternative fuels.